Evaluation of Self-Contained PACS Viewers on CD-ROM. - Hosch, Richard; Rivard, Andrew (Journal of Digital Imaging, 2014)
Providing patients and clinicians with self-contained PACS viewer on CD format is a common and necessary tool to share vital imaging data. However, to be useful, this tool should be reliable, robust, and convenient. Numerous PACS viewer options are available, often without empirical data to guide in choosing one for routine use. To assist in making a standardized choice for our institution, we chose four common viewers, benchmarked on four different workstations reflecting the variety of environments used by non-radiologist clinicians who would receive a CD. Four CD-based DICOM viewers from eFilm, Philips, Pacsgear Gearview, and iSite were examed on two radiology PACS workstations, a standard desktop computer, and a laptop using a test case consisting of a multi-series CTA with 13 series and 3,035 total images. Multiple objective measures, subjective measures, and presence of key features were evaluated including program time to load, image time to load, cine/movie mode, ability to adequately window and level, pan and zoom functionality, basic measurement tools, and perceived lag when scrolling through a multi-image series. Substantial differences in speed of operation and behavior on multiple systems were documented, which could potentially add several minutes to the time required to open and view a patient's imaging data. The eFilm and iSite viewers operated consistently and reliably across all tested computer environments. The iSite viewer, having among the quickest load times in the group tested and consistently low subjective scroll lag during series viewing, and also beneficially allowing partial viewing while images load in the background, was found to generate the best overall user experience. Because of these significant differences, we have recommended that our institution standardize all patient imaging CD creation using the iSite viewer.